THE IMPLEMENTATION OF REGIONAL CIVIL SERVANT INVESTIGATOR IN LAW ENFORCEMENT IN KUNINGAN DISTRICT, INDONESIA - Ade Suhendra; Haris Budiman; Erga Yuhandra (UNIFIKASI : Jurnal Ilmu Hukum, 2019)
This research aims to analyze the regulation of Civil Servant Investigator based on Regional Regulation No. 6 of 2005 and the implementation of Regional Regulation No. 6 of 2005 concerning Regional Civil Servant Investigator at Office of Kuningan District Civil Service Police Unit. This descriptive-analytical research applied a normative juridical approach. The results showed that based on Regional Regulation No. 6 of 2005, Regional Civil Servant Investigator has the duties of conducting investigation on violations of Regional Regulations in which each Regional Civil Servant Investigator must be equipped with an investigation warrant signed by the supervisor of the Regional Civil Servant Investigator in conducting the investigation. Besides, Regional Civil Servant Investigator also has the duties of providing coaching which includes general, technical, and operational coaching for Civil Servant Investigator. Further, regarding the implementation of Regional Regulation No. 6 of 2005 concerning Regional Civil Servant Investigator at Office of Kuningan District Civil Service Police Unit, the Regional Civil Servant Investigator generally has carried out its duties in conducting investigation and inspection towards illegal buildings, places of business and business activities; conducting investigation and inspection towards community, apparatus or legal entities violating regional regulations, head district regulations, and head district decisions; and preparing material to be submitted to the National Police regarding follow up actions towards community, apparatus or legal entities violating regional regulations, head district regulations, and head district decisions. Thus, it can be concluded that, in general, Regional Regulation No. 6 of 2005 concerning Regional Civil Servant Investigator at Office of Kuningan District Civil Service Police Unit has been implemented well.Tujuan penelitian ini yaitu untuk mengetahui Penyidik Pegawai Negeri Sipil berdasarkan Peraturan Daerah Nomor 6 Tahun 2005 dan implementasi Peraturan Daerah Nomor 6 Tahun 2005 tentang Penyidik Pegawai Negeri Sipil Daerah di Kantor Satpol Polisi Pamongpraja Kabupaten Kuningan. Spesifikasi penelitian yang digunakan adalah penelitian bersifat deskriptif-analitis dengan pendekatan yuridis normatif. Hasil penelitian menunjukkan bahwa pengaturan Penyidik Pegawai Negeri Sipil berdasarkan Peraturan Daerah Nomor 6 Tahun 2005 dijelaskan bahwa Penyidik Pegawai Negeri Sipil Daerah mempunyai tugas melakukan penyidikan atas pelanggaran Peraturan Daerah; setiap Penyidik Pegawai Negeri Sipil Daerah dalam menjalankan tugas penyidikan harus dilengkapi dengan surat perintah penyidikan yang ditanda tangani oleh atasan Penyidik Pegawai Negeri Sipil Daerah; serta pembinaan terhadap Penyidik Pegawai Negeri Sipil meliputi: pembinaan umum, pembinaan teknis, dan pembinaan operasional. Selanjutnya implementasi Peraturan Daerah Nomor 6 Tahun 2005 tentang Penyidik Pegawai Negeri Sipil Daerah di Kantor Satpol PP Kabupaten Kuningan secara umum Penyidik Pegawai Negeri Sipil Daerah telah melaksanakan penyelidikan, penyidikan, dan pemeriksaan terhadap bangunan, tempat-tempat usaha dan kegiatan usaha tanpa izin; melaksanakan penyelidikan, penyidikan, dan pemeriksaan terhadap masyarakat, aparatur atau badan hukum yang melakukan pelanggaran atas peraturan daerah, peraturan bupati, dan keputusan bupati; dan menyiapkan bahan koordinasi kepada Keolisian Negara mengenai tindak lanjut berita acara pemeriksaan warga masyarakat, aparatur atau badan hukum yang melakukan pelanggaran atas peraturan daerah, peraturan bupati, dan keputusan bupati. Kesimpulan penelitian yaitu implementasi Peraturan Daerah Nomor 6 Tahun 2005 tentang Penyidik Pegawai Negeri Sipil Daerah di Kantor Satpol Polisi Pamongpraja Kabupaten Kuningan secara umum sudah dilaksanakan dengan baik.